The System Usability Scale: Past, Present, and Future - Lewis, James R. (International journal of human-computer interaction, 2018)
The System Usability Scale (SUS) is the most widely used standardized questionnaire for the assessment of perceived usability. This review of the SUS covers its early history from inception in the 1980s through recent research and its future prospects. From relatively inauspicious beginnings, when its originator described it as a "quick and dirty usability scale," it has proven to be quick but not "dirty." It is likely that the SUS will continue to be a popular measurement of perceived usability for the foreseeable future. When researchers and practitioners need a measure of perceived usability, they should strongly consider using the SUS.